Actual and potential distribution of Pinus engelmannii Carriére under climate change scenarios - Jiménez Salazar, Miguel Ángel; Méndez González, Jorge (Instituto de Ecología, A.C., 2021)
Ecological niche models (ENMs) are a tool to understand the impact of climate change on the distribution of species. The objective of this study was to generate ENMs to predict the current and potential distribution of Pinus engelmannii Carriére. The models were created in ‘kuenm’, an R package that uses Maxent as modelling algorithm. We used 364 meticulously cleaned species occurrence records, 15 bioclimatic variables, and climatic projections from four General Circulation Models (CGMs) to 2050, under two Representative Concentration Pathways (RCPs) 4.5 and 8.5. The ENMs were evaluated according to their statistical significance, partial ROC, omission rate (<5%), AIC, and response of the variable. A total of 1827 candidate ENMs were generated, the one that showed the best performance was of quadratic type. Bio 1 [Average annual temperature (ºC)] and Bio 17 [Precipitation of ¼ driest annual (mm)], are the variables that best predict the distribution of P. engelmannii, contributing to the model with 75.6% and 6.3%. The areas of high suitability for this species occur discontinuously in Chihuahua (29 090 km2) and Durango (9310 km2) states; their preferences are between 9 ºC and 12 ºC (Bio 1). Apparently, this species is not susceptible to climate change, because when transferring the model and despite an increase of almost 2 ºC (Bio 1) to the year 2050 in its current distribution, no new suitable areas are predicted, but neither the existing ones are lost.